Rumusan Alternatif Strategi Pemasaran Olahan Pangan Kue Nopia di Desa Pakunden Kecamatan Banyumas Kabupaten Banyumas - Ardani, Novi Dwi; Utami, Pujiati; Dumasari, Dumasari; Watemin, Watemin (Proceedings Series on Physical & Formal Sciences, 2021)
This study aimed to determine the formulation of an alternative marketing strategy for processed nopia cakes in Pakunden Village, Banyumas District, Banyumas Regency. The research was conducted in February – March 2021 in Pakunden Village, Banyumas District, Banyumas Regency. The number of samples in this study was 26 respondents of nopia maker. The study results stated that the formulation of an alternative marketing strategy for nopia cakes in Pakunden Village, Banyumas District, Banyumas Regency, was to increase the sales production process by maintaining the quality and price of competitors, mastering marketing areas and new customers, take advantage of existing technology to promote it more broadly, expand the place of manufacture and open outlets so that consumers are more familiar with them, has many taste innovations in nopia, and it adds to the workforce in the nopia cakes.